Timing and intensity of proton pump inhibitor exposure hampers overall survival in patients with metastatic non-small cell lung cancer treated with immune checkpoint inhibitors: a retrospective cohort study - Japelj, Nuša; Horvat, Nejc; Jazbar, Janja; Kos, Mitja; Kapušin, Veronika Pelicon; Knez, Lea (Frontiers in Immunology, 2026)
IntroductionProton pump inhibitor (PPI) use has been associated with reduced immune checkpoint inhibitor (ICI) efficacy in metastatic non-small cell lung cancer (mNSCLC) with evidence limited to their use during a short time period around ICI initiation. This study evaluated the associations between the timing and intensity of PPI exposure up to one year before ICI initiation and overall survival (OS) in mNSCLC patients treated with ICIs.MethodsThis retrospective cohort study included consecutive mNSCLC patients treated with ICIs within routine clinical practice. Patients were grouped by the timing of PPI exposure from 365 days before to 30 days after (−365 to +30 days) ICI initiation: (1) no PPIs within −365 to +30 days; (2) PPIs only within −365 to −31 days; and (3) PPIs also within ±30 days of ICI initiation. The intensity of PPI exposure was quantified with the total defined daily doses (DDDs). OS was estimated using Kaplan–Meier methods, and associations between PPI exposure and OS were analyzed using Cox proportional hazards models.ResultsOf 391 patients included (median age 64.7 years, 58.6% male), 73.4% had access to PPI within −365 to +30 days of ICI initiation. PPI exposure within ±30 days (220 patients) was associated with reduced median OS (mOS) compared with no PPI exposure between −365 and +30 days of ICI initiation (mOS 15.4 vs 21.9 months; adjusted hazard ratio [aHR] 1.373, 95% CI 1.007–1.873, p = 0.045). High-intensity PPI exposure within −365 to +30 days of ICI initiation (DDD > 159; 108 patients) was also associated with reduced mOS compared with no PPI exposure in this period (mOS 13.4 vs 21.9 months; aHR 1.454, 95% CI 1.023–2.067, p = 0.037).DiscussionPPI use around ICI initiation as well as PPI treatment intensity over a wider period was associated with reduced OS. Efforts should be made to streamline PPI use.